Non‐rhabdomyosarcoma soft tissue sarcomas diagnosed in patients at a young age. An overview of clinical, pathological, and molecular findings. Issue 8 (25th March 2021) - Renzi, Samuele; Cullinan, Noelle; Cohen‐Gogo, Sarah; Langenberg‐Ververgaert, Karin; Michaeli, Orli; Alkendi, Jalila; Kanwar, Nisha; Lo, Winnie; Villani, Anita; Shlien, Adam; Malkin, David; Ryan, Anne L.; et al.
Abstract: Objective: Disease spectrum in pediatric sarcoma differs substantially from adults. We report a cohort of very young children with non‐rhabdomyosarcoma soft tissue sarcoma (NRSTS) detailing their molecular features, treatment, and outcome. Methods: We report features of consecutive children (age <2 years) with NRSTS (2000–2017). Archival pathological material was re‐reviewed, with additional molecular techniques applied where indicated. Results: Twenty‐nine patients (16 females, 55%) were identified (median age 6 months; range 0–23). Most common diagnoses included infantile fibrosarcoma (IFS, n = 14, 48%), malignant rhabdoid tumor (MRT, n = 4, 14%), and undifferentiated sarcoma ( n = 4, 14%). Twenty‐seven of 29 (93%) had tumor molecular characterization to confirm diagnosis. Clinical presentation included a swelling/mass ( n = 23, 79%). Disease extent was localized ( n = 20, 69%), locoregional ( n = 6, 21%), or metastatic ( n = 3, 10%). Seventeen of 29 (59%) who underwent surgery achieved complete resection (R0). Other treatments included conventional chemotherapy ( n = 26, 90%), molecularly targeted therapies ( n = 3, 10%), and radiation ( n = 5, 17%). At last follow‐up (median 3 years; range 0.3–16.4), 23 (79%) were alive, disease‐free and six (21%) had died of disease. All patients with IFS were alive and all those with MRT died. A cancer predisposition syndrome (CPS) was confirmed in three of 10 (30%) genetically tested patients. Conclusion: We recommend tumor molecular characterization in all young patients including evaluation for CPS to optimize treatment options and prognostication.